Primary Adenosquamous Carcinoma of the Prostate with Rectal Invasion - Pierre Azzi; Dominique Bossé; Ilias Cagiannos; Paul Borowy-Borowski; David Tiberi (Case Reports in Urology)
Prostate adenosquamous carcinoma (pASC) is a rare form of prostate cancer accounting for <1% of all cases. It is generally considered an aggressive variant often presenting with significant symptom burden and/or metastatic disease. Given its rarity, optimal management of this cancer is unknown. We present a case of a patient with pASC treated with radiotherapy and chemotherapy with excellent symptomatic improvement and local control.